Factors associated with quality of life among joint and nuclear families: a population-based study - Fahad Saqib Lodhi; Unaib Rabbani; Adeel Ahmed Khan; Owais Raza; Kourosh Holakouie-Naieni; Mehdi Yaseri; Umer Farooq; Ali Montazeri (BMC, 2021)
Abstract Background Advantages and disadvantages associated with joint and nuclear family systems can affect quality of life (QOL). However, there is scarcity of literature about QOL among joint and nuclear family systems. This study aimed to assess the factors associated with QOL in joint and nuclear family systems. Methods We conducted a population based cross sectional study in all 52 Union Councils (UCs) of District Abbottabad, Khyber Pakhtunkhwa province, Pakistan from March 2015 to August 2015. Multistage cluster sampling technique was used to select participants from both nuclear and joint family houses. The validated Urdu version of World Health Organization Quality of Life Questionnaire-Brief Version (WHOQOL-BREF) was used to assess quality of life among participants. Univariate and multivariate analyses were performed to explore the associations of different socio demographic variables with QOL among both family systems. Also a multilevel linear regression using backward analysis to obtain final model for each domain was performed to find out the variables that are associated with QOL score in each of family systems. Results A total of 2063 participants were included in this study (51.0% joint family, 49.0% nuclear family) with the response rate of 97.4%. In multiple linear regression analysis of each domain for joint and nuclear family systems, rural residence compared to urban (p < 0.001), being female (p < 0.001), older age (p < 0.001), having comorbidity (p < 0.001) and lower socioeconomic status (p < 0.001) were found to be a strong predictor of poorer QOL. Furthermore, social capital (p < 0.001) had a positive effect on joint and nuclear family QOL scores. Conclusion This study was the first of its kind which determined the factors of QOL in joint and nuclear families using the validated Urdu version of WHOQOL-BREF in Pakistan. Male gender, urban residence, younger age, higher socioeconomic status and social capital were positive predictors of QOL score while older age and presence of illness were associated with lower QOL scores among both family systems.